Hubungan Antara Motivasi Belajar dengan Hasil Belajar Siswa dalam Pembelajaran IPA di Sekolah Dasar - Monica Feri Yolanda; Syamsu Arlis (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The research aim to know there is or no correlation between students motivation in learning with learning outcomes in natural sciences learning of fifth grade of primary school on cluster three in Banuhampu. This type of research is quantitative research with correlation research methods. The amount of sample is 57 students, fifth grade of primary school on cluster three in Banuhampu. The result of the research there is positive correlation an significant between students motivation in learning with learning outcomes in natural sciences learning of fifth grade of primary school on cluster three in Banuhampu. This was proven from rhitung = 0.789 > rtabel = 0.266, and significance value 0.000 < 0.005. 005, which means that Ho is rejected and Ha is accepted, so the hypothesis says "there is a correlation between students in learning motivation with learning outcomes in natural science learning in of fifth grade of primary school on cluster three in Banuhampu" accepted.Keywords :